Variabilidad y distancia geneticas de razas y cruces bovinos en Cuba - Ronda, R.=700 1 Perez-Beato, O.; Granado, A.; Fernandez, M.H
(Es, En)
Ilus., 15 ref.
Keywords: GANADO BOVINO; RAZAS (ANIMALES); VARIACION GENETICA; DISTANCIA GENETICA; CUBA; RAZAS HOLSTEIN-FRIESIAN; CEBU CUBANO; REVISTA DE SALUD ANIMAL